Impact factors for Adolescents’ Emotion Regulation Ability and Choice of Strategy: An Overview - Zhu, Zhengrong (Transactions on Social Science, Education and Humanities Research, 2024)
This study aimed to explore the importance and influence factors of adolescents’ emotion regulation (ER). This study approached research purpose by summarizing and analyzing four major influencers of ER in adolescents: age, parental styles, culture, and education. As found, at a young age, adolescents show a lower ability to regulate emotions due to the development of the “hot system” and low Self Control (SC). Then, this study discussed the impact of parenting styles (PS) on adolescents’ ER. Different PSs may indirectly lead to different ER abilities in their children. Past literature also presented that culture may influence children’s choice of ER strategy. Two ER strategies were introduced to address cultural preferences for using them. Last, the teacher and positive education intervention’s impact on students’ ER ability was discussed. For future direction, it was suggested that more research be done on cultural influence on ER in adolescents.